To be a chick mother : variation in maternal care and its effect on chick behavioural development - Christenson, Linnéa (SLU/Dept. of Animal Nutrition and Management (until 231231), 2021)
In Swedish poultry production today over 7 million chicks are incubated, housed and reared without maternal care. Studies indicate that chicks behavioural development and welfare may benefit from hen maternal care and potentially maternal care could be artificially provided in the commercial situation. However, hen maternal abilities vary, which affect chick behavioural development. The aim of this study was to in-vestigate maternal variation (social status and type of broodiness) in the maternal care between different hens (H) and how this variation affect the behavioural development of the chicks (C). The hens’ social status (dominant or submissive) in the adult group affect the learning ability in other adults, the hens type of broodiness (induced broody or natural broody) affect when the maternal hormones in the hens body are released, both of which might affect the chicks behavioural development. Old Swedish bantam hens and Bovans Robust chicks were used in this trial. Hen social status (dominant D or submissive S) in the adult group was determined with a social interaction test. Family groups were formed by putting six chicks with a hen. Control groups were six chicks without a hen. Chicks were brooded either under nat-urally broody hens (natural broody NB) or in an incubator and later put with the hen (induced broody IB). Behavioural testing of the chicks was made on day four, five, 10, 18 and 26 and feather scoring was done at day 27 post hatch. The chicks wound score was analyzed in the end of each group’s testing period. In total seven family groups and three control groups were recorded and analyzed in this trial. Four hens were defined as dominant, three as submissive, four as natural broody and three as induced broody. Hens differed significantly in purring and chick latency to approach. The chick group spread varies with the chicks ability to ther-moregulate, close at first and further away for older chicks, unexpectedly the domi-nant hen’s chicks keeps the same distance the entire time. Foraging behaviour did not differ, however on recording day 10 and 18 feather pecking behaviour differed be-tween the family groups and control groups and between the natural broody and the induced broody groups. Hen individual maternal behaviour showed large variation e.g. showing as differ-ent feather and wound scores. Based on the chicks feather and wound plumage the best family groups where ID3(S and NB) and ID7(D and IB) and the worst was ID6 (D and IB). Based on this study it is important to choose the best individual mother hens for the chicks. However, further research is necessary to define which mother hen characteristics that benefit chick behavioural development. As a general conclusion, the control chicks in this trial showed less variation com-pared to chicks reared with a mother hen. In conclusion, during rearing the individual hen can favor while another can disfavor chick behavioural development, compared to chicks reared without a mother hen.